SERVİKAL YARALANMALARDA HALO-VEST TEDAVİSİ: - TANRIVERDİ, Taner; AK, Halil; TÜRECİ, Ercan; HANCI, Murat; KUDAY, Cengiz (Cerrahpaşa Medical Journal, 2019)
Background.- In this report, we try to describe the halo-vest treatment in patients with cervical spine õnjuries. The complications as a consequence halo-vest treatment also have discussed in the light of the literature. Design.- The study included the 55 consecutive patients who admitted to the Emergency Department of Cerrahpasa Medical School between 1986 and 2001 and who were treated by halo-vest. Results.- Forty-five of 55 patients were treated solely by halo-vest conservatively but 10 patients were required surgical intervention as anterior/posterior fusion following halo-vest. Twenty-four of 29 patients with upper cervical injuries and 21 of 26 patients with lower cervical injuries were treated by halo-vest successfully. The success rate in this series was found to be 96.6 %. Conclusion.- Although there are some complications as in all treatment modalities, the halo-vest is considered by us to be the best commercially available orthosis for control of the cervical spine in case of injury. Furthermore, we think that if applied properly, the number of the complications related to the halo-vest will be reduced and success rate will be high.